PELAYANAN PUBLIK PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL DI KABUPATEN BUTON SELATAN - Fadli, Muhammad; Adys, Abdul Kadir; Riskasari, Riskasari (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2023)
The results of the study showed that the public service at the Department of Population and Civil Registration in South Buton Regency. The implementation had been optimal but it could not be said to be effective as a whole. This was seen in several indicators, namely (1) Dimensions of tangibles related to facilities and infrastructure as well as service support facilities at the Department of Population and Civil Registration office of South Buton Regency were still inadequate so they still needed to be improved. (2) The dimensions of employee reliability in providing services had been optimal but it still needed to increase the number of employees so that the existing services were even better. (3) Dimensions Responsiveness was response of employees in providing services to the community was optimal. (4) Dimensions of assurance estimated service in the completion of the document was not on time yet. (5) Dimensions of Empathy employees had  a good service, they were sincere and give attention. Also, they did not discriminate the community in providing services.